Genus-Wide Assessment of Antibiotic Resistance in Lactobacillus spp - Campedelli, Ilenia; Mathur, Harsh; Salvetti, Elisa; Clarke, Siobhán; Rea, Mary C.; Torriani, Sandra; Ross, R. Paul; Hill, Colin; O’Toole, Paul W. (Applied and environmental microbiology, 2019)
Lactobacillus species are generally considered to be nonpathogenic and are used in a wide variety of foods and products for humans and animals. However, many of the species examined in this study have antibiotic resistance levels which exceed those recommended by the EFSA, suggesting that these cutoff values should be reexamined in light of the genetic basis for resistance discussed here. Our data provide evidence for rationally revising the regulatory guidelines for safety assessment of lactobacilli entering the food chain as starter cultures, food preservatives, or probiotics and will facilitate comprehensive genotype-based assessment of strains for safety screening. Lactobacillus species are widely used as probiotics and starter cultures for a variety of foods, supported by a long history of safe usage. Although more than 35 species meet the European Food Safety Authority (EFSA) criteria for qualified presumption of safety status, the safety of Lactobacillus species and their carriage of antibiotic resistance (AR) genes is under continuing ad hoc review. To comprehensively update the identification of AR in the genus Lactobacillus , we determined the antibiotic susceptibility patterns of 182 Lactobacillus type strains and compared these phenotypes to their genotypes based on genome-wide annotations of AR genes. Resistances to trimethoprim, vancomycin, and kanamycin were the most common phenotypes. A combination of homology-based screening and manual annotation identified genes encoding resistance to aminoglycosides (20 sequences), tetracycline (18), erythromycin (6), clindamycin (60), and chloramphenicol (42). In particular, the genes aac(3) and lsa , involved in resistance to aminoglycosides and clindamycin, respectively, were found in Lactobacillus spp. Acquired determinants predicted to code for tetracycline and erythromycin resistance were detected in Lactobacillus ingluviei , Lactobacillus amylophilus , and Lactobacillus amylotrophicus , flanked in the genome by mobile genetic elements with potential for horizontal transfer. IMPORTANCE Lactobacillus species are generally considered to be nonpathogenic and are used in a wide variety of foods and products for humans and animals. However, many of the species examined in this study have antibiotic resistance levels which exceed those recommended by the EFSA, suggesting that these cutoff values should be reexamined in light of the genetic basis for resistance discussed here. Our data provide evidence for rationally revising the regulatory guidelines for safety assessment of lactobacilli entering the food chain as starter cultures, food preservatives, or probiotics and will facilitate comprehensive genotype-based assessment of strains for safety screening.